1985
DOI: 10.2307/1956248
|View full text |Cite
|
Sign up to set email alerts
|

Attitude Attribution: A Group Basis for Political Reasoning

Abstract: This article shows that citizens can estimate what politically strategic groups—liberals and conservatives, Democrats and Republicans, and blacks and whites—stand for on major issues. These attitude attributions follow from a simple calculus, a likability heuristic. This heuristic is rooted in people's likes and dislikes of political groups. Thanks to this affective calculus, many in the mass public are able to estimate who stands for what politically, notwithstanding shortfalls in information and information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
233
0
4

Year Published

1991
1991
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 451 publications
(253 citation statements)
references
References 18 publications
15
233
0
4
Order By: Relevance
“…That the thermometer measures global evaluations of the parties is not only obvious on the surface but has been established by previous research (Wiesberg and Rusk 1970;Rabinowitz 1972). Similarly, ratings of social groups using the thermometer have been used in earlier research both as a component of group consciousness and as a cognitive heuristic that helped people "figure out the issue positions of strategic groups" (Brady andSniderman 1985, 1062).…”
Section: A the Prevalence Of Group Thinkingmentioning
confidence: 92%
See 1 more Smart Citation
“…That the thermometer measures global evaluations of the parties is not only obvious on the surface but has been established by previous research (Wiesberg and Rusk 1970;Rabinowitz 1972). Similarly, ratings of social groups using the thermometer have been used in earlier research both as a component of group consciousness and as a cognitive heuristic that helped people "figure out the issue positions of strategic groups" (Brady andSniderman 1985, 1062).…”
Section: A the Prevalence Of Group Thinkingmentioning
confidence: 92%
“…Previous research reveals that along with candidates, issues, and political parties, groups are one of the major foci people use in organizing their general political cognitions (Lau 1986;Hamill, Lodge, and Blake 1985). There is also growing evidence that evaluations and cognitions involving social groups influence a variety of political attitudes including political ideology and policy preferences (Brady and Sniderman 1985;Sears et al 1980), evaluations of government economic performance (Conover 1987) and beliefs about the distribution of power and equity in America Dennis 1987). Much less attention, however, has been given to the role of social groups in structuring partisan evaluations and cognitions, the central focus of this article.…”
Section: Introductionmentioning
confidence: 99%
“…A fourth strand, closely related to the third, consists of a group of scholars seeking to understand how it is that citizens reason about politics, combining political science with social and cognitive psychology (Brady and Sniderman 1985;Conover and Feldman 1989;Fiske 1986;Hamill, Lodge, and Blake 1985;Sniderman, Brody, and Tetlock 1991). Some in this fourth tradition have attempted to ascertain whether citizens are able to overcome their information shortfalls by using a series of cognitive tools (Brady and Sniderman 1985;Sniderman, Brody, and Tetlock 1991).…”
Section: The Uninformed Citizen -The Role Of Information In Voting Bementioning
confidence: 99%
“…Some in this fourth tradition have attempted to ascertain whether citizens are able to overcome their information shortfalls by using a series of cognitive tools (Brady and Sniderman 1985;Sniderman, Brody, and Tetlock 1991). These scholars have suggested that perhaps individuals use heuristics or information "short-cuts" to come to the same decisions they would make if they were fully informed.…”
Section: The Uninformed Citizen -The Role Of Information In Voting Bementioning
confidence: 99%
See 1 more Smart Citation